2021
DOI: 10.3389/fmolb.2021.716477
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Binding Transition State After the Conformational Selection Step: The Second Half of the Molecular Recognition Process Between NS1 of the 1918 Influenza Virus and Host p85β

Abstract: Biomolecular recognition often involves conformational changes as a prerequisite for binding (i.e., conformational selection) or concurrently with binding (i.e., induced-fit). Recent advances in structural and kinetic approaches have enabled the detailed characterization of protein motions at atomic resolution. However, to fully understand the role of the conformational dynamics in molecular recognition, studies on the binding transition state are needed. Here, we investigate the binding transition state betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Recently, we determined the thermodynamic and kinetic contributions of p85β-binding surface residues on NS1 and revealed that I145 ( Figure 4 A) plays an important role in stabilizing both binding transition and complex states. 18 …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we determined the thermodynamic and kinetic contributions of p85β-binding surface residues on NS1 and revealed that I145 ( Figure 4 A) plays an important role in stabilizing both binding transition and complex states. 18 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Thus, ϕ-value analysis is a critical tool for the mechanistic understanding of binding kinetics and thermodynamics. 18 , 32 34 …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ). The p85β-binding interface on NS1 consists of 20 residues based on the crystal structure of the complex 23 , 29 , while our previous study identified residues 89, 95, 98, 145, and 146 of NS1 as the major players determining the p85β-binding rate constant 29 ; thus, these residues are referred to as core interface residues (Fig. 2a ).…”
Section: Resultsmentioning
confidence: 99%
“…S3 ). The p85β-binding interface on NS1 consists of 20 residues based on the crystal structure of the complex ( 23, 29 ), while our previous study identified residues 89, 95, 98, 145, and 146 of NS1 as the major players determining the p85β-binding rate constant( 29 ); thus, these residues are referred to as core interface residues ( Fig. 2A ).…”
Section: Resultsmentioning
confidence: 99%